Traumatizing the traumatized: self-harm and death in women’s prisons in England and Wales - Atkinson, Kym (Feminist responses to injustices of the state and its institutions, 2024)
This chapter is concerned with utilizing feminist methodology and theory to critique the dominant discourses surrounding self-harm and death in women’s prisons. First, it provides a critical overview of the data concerning harm and deaths in women’s prisons. Second, it considers how a feminist epistemology built on ‘feminist praxis’ can be used to ‘unsilence’ the voices of women in prison, and their families, and place their experiences directly at the centre of knowledge production. Third, it develops a feminist, theoretical perspective in order to critically conceptualize the nature of life and death in women’s prisons. Finally, the chapter outlines a number of feminist-based strategies and interventions for the prevention and elimination of self-harm and deaths in prisons. These strategies are put forward to contribute to the radical transformation in, and eventual abolition of, a pain-inducing institution which is dangerous to women.